Governing Marginality: Coercion and Care in Probation. (6th January 2021) - Phelps, Michelle S; Ruhland, Ebony L
Abstract: While the scale and consequences of mass incarceration in the United States have been well-documented over the past two decades, sociologists have focused less attention on mass probation and the expansion of community supervision. Originally designed as a rehabilitative alternative to imprisonment, probation represents the largest form of penal control and a critical intersection between criminal justice and welfare—two systems that govern citizens at the margins. We analyze qualitative data from over 100 focus groups conducted in 2016-2017 with adults on probation and probation officers in several jurisdictions across the country to show the enmeshing of coercion and care in probation. Drawing on the concept of carceral citizenship, we detail the duties, burdens, and perverse benefits of supervision across four domains: relationships with probation officers, access to services and programs, time and financial constrictions, and the threat of revocation (or incarceration for non-compliance). We argue that probation provides barebones welfare services for some of the most vulnerable adults, while also imposing the unique harms of a criminal record, burdens of supervision, and risk of incarceration.